Characterization of protease from thermophiles isolated from Local Hot Springs / Mohd Nur Fakhruzzaman Noorizhab - Noorizhab, Mohd Nur Fakhruzzaman (2012)
To obtain enzymes with improved thermostability, many have resort to isolate enzymes from naturally occuring thermophilic organisms. However, the disadvantage is that it is often difficult to get good yield. Hence this study was undertaken to investigate the thermophilic protease production in eight isolated thermophiles (A I, A3, A4, AS, A6, A8, A13 and A14) by both biochemical PCR. All the eight thennophiles were subjected to skim milk agar assay to detect protease enzyme and further amplified by PCR for protease gene. All the eight thermophiles were positive for protease gene but in skim milk assay, only A 1, A3, A4, A6 and A8 demonstrated hydrolysis. Comparative analysis amongst these eight indicated that AS had the highest proteolytic activity and therefore was further examined its potentials. A8 was found to be motile, Gram positive rod with endospore, catalase positive, oxidase negative and is a glucose, sucrose, fructose fermenter except maltose. The protease enzyme was stable at 55°C to 75°C and was most active at pH 7. Furthermore, AS protease activity was inhibited by 5 mM ethyldiaminetetraacetyl acid and 5 mM phenysulphonylmethylfluoride thus indication that it produced two types of proteases; metalloproteases and serine proteases. Further indentification by 16S rRNA gene sequencing revealed that it is closely related to Geobacillus thermocatenulatus strain BGSC 93A 1 with 70% similarity to peptidase of Geobacillus sp. strain C56-T3 (Accession No. CP002050.1 ), Geobacillus sp. strain Y 412MC61 (Accession No. CPOO 1794.1) and Geobacillus kaustophilus strain HT A426 (Accession No. BA000043.1 ). The protease fragment sequence of Geobacillus sp. strain AS was submitted to GenBank (Accession No. JF960945) where it codes for SS peptidase group (a group for serine-type protease). Molecular weight determination by SDSPAGE for AS was found to be 20-27 kDa. The total protease activity by fermentation study was 185 U/ml. In conclusion this study had successfully isolated a thermostable protease producer identified as Geobacillus sp. A8 based on I 6S rRNA and biochemical analysis.